(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: To evaluate temporomandibular disorders before and after orthognathic surgeries. Materials & methods: A total of 40 patients were enrolled. Assessment of temporomandibular status was performed using the RDC/TMD criteria at T0 (prior to orthodontic therapy), T1 (3 months after the surgery), and T2 post-therapeutic cycle (6 to 12 months postoperatively). Result was analysed using SPSS software. Results: At T1, 3 months after the orthognathic surgery, TMJ pain changed from 45% to 5%, headaches improved from 40% to 7.5% and disc dislocation from 52.5% to 20%. The most significant results can be seen from the comparison between T0 and T2 period. Conclusion: Pain levels related to TMDs can be significantly improved with a multi-disciplinary approach